Ethics for journalists [electronic resource] - Keeble, Richard , 1948- (Media skills, 2009)
Tackles many of the issues which journalists face in their everyday lives - from the media's supposed obsession with sex, sleaze and sensationalism, to issues of regulation and censorship. This book